Fachsprachen im DaF-/DaZ-Unterricht - Balbiani, Laura (Kritik. Rivista di letteratura e critica culturale, 2023)
At many schools, foreign languages are increasingly being combined with specific contents and subjects, both for integrative teaching (CLIL methodologies) and as a support focus in the ‚scuole tecniche e professionali‘. At university, the so-called ‚Mediazione linguistica‘-courses are offering such a combination. The teaching thus aims to prepare learners for the communicative requirements in foreign professional contexts. The goal is achieved by focusing on action-oriented and communicative skills with regard to a professional qualification. This paper presents goals and strategies that can be implemented in DaF-teaching in order to acquire and practice LSP. In particular, the following themes will be addressed: Planning and goals of subject-related teaching (selection of materials; macro- and microsequencing of a teaching unit); characteristics of specialised texts and how to work them out in teaching; exercise typologies (for oral, written and intercultural communication).